Fiqih Learning Method According To Hasan Ja'far Kholifah And Kamaluddin Muhammad Hasyim - 'Azizah, Alviatul; Basuki, Basuki (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
Fiqh is a science that explains Islamic laws. To be able to convey this knowledge, there is a need for a fiqh learning method so that it can be well received by students. This research aims to describe the method of learning fiqh according to the thoughts of Hasan Ja'far Kholifah and Kamaluddin Muhammad Hasyim in their book entitled